Analisis Lama Waktu Pemanasan dan Rasio Komposisi Oli terhadap Peningkatan Kualitas Batubara menggunakan Metode Upgrading Brown Coal - Ferry Samuel Maringan Siregar; Windhu Nugroho; Henny Magdalena; Agus Winarno; Rety Winonazada (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
Low-rank coal generally has a high moisture content, which results in a low calorific value and suboptimal quality for utilization as an energy source. One method that can be applied to improve coal quality is the Upgrading Brown Coal (UBC) process, which functions to reduce moisture content and increase fixed carbon value. This study aims to analyze the effect of heating time and the ratio of used oil composition on improving coal quality based on proximate parameters. The research method includes collecting coal samples from four locations in Samarinda and its surrounding areas, namely SMAN 1 Samarinda, Bhineka Street, Palaran Stadium, and Tani Bakti Village. The samples were analyzed using proximate analysis, including inherent moisture (IM), ash content (AC), volatile matter (VM), and fixed carbon (FC), both before and after the UBC process. The upgrading process was carried out with variations in heating time and used oil composition as a coating medium to enhance coal stability and prevent moisture reabsorption. The final results of the upgrading process showed the best values of inherent moisture at 13.64%, ash content at 4.66%, volatile matter at 55.06%, and fixed carbon at 44.94%. The results indicate that the UBC process is capable of reducing inherent moisture and increasing fixed carbon, thereby improving coal quality. Variations in heating time and used oil composition have a significant effect on changes in proximate parameters. Longer heating time and an appropriate ratio of used oil composition result in a more optimal improvement in coal quality.